Site-Specific Evolution of Surface Stress during the Room-Temperature Oxidation of the Si(111)-(7x7) Surface. - BOLAND, JOHN; KINAHAN, NIALL; MEEHAN, DAVID (My University, 2010)
The reaction of molecular oxygen with the Si(111)-7?7 surface is investigated at room temperature using in situ scanning tunneling microscopy and surface stress measurements to reveal the quantitative relationship between site-specific oxygen coverage and a decrease in tensile surface stress. This relationship is described using a modified form of the reaction model originally proposed by Dujardin et al. We show that the decrease in tensile surface stress is greatest for the faulted subunits of the 7?7 cell and determine the stress signatures of different reaction products, including the absence of long-lived metastable species with a unique stress signature.
PUBLISHED
Article No: 146101
Keywords: Chemistry; Neuroscience